Development of Busy Book Media in Introducing Gender Roles to Children Aged 4-6 Years in Pangkalpinang City - Withasari, Yurinda; Putri, Dian Puspita Eka; Novitasari, Rezki Juniarti (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to introduce gender roles to children using busy books. This research is a research and development study using the ADDIE method. The sample of this study was 5 educators and 25 children in Pangkalpinang City. The learning plan was prepared quite well by the educators. There are four methods used: habituation, storytelling, and conversation. The media used was busy books. Changes in children's learning behavior include children being able to recognize the gender roles of boys and girls. The results of this study indicate that busy books are suitable for introducing children to gender roles.